WAYS FOR A LEADER TO WORK ON SPEECH AND IMPROVE SPEAKING SKILLS (American Journal of Pedagogical and Educational Research, 2023)
The article analyzes issues such as the management process and the formation of the leader as a speaker, the history of the study of management as a theoretical science, the art of management, the influence of management, management psychology, social psychology, and the leader's social role in management.